A long-run perspective on the spatial concentration of manufacturing industries in the United States - Nicholas F. R. Crafts; Alexander Klein (University of Kent, School of Economics, 2017)
We construct spatially-weighted indices of the geographic concentration of U.S. manufacturing industries during the period 1880 to 1997 using data from the Census of Manufactures and Bureau of Labor Statistics. Several important new results emerge from this exercise. First, we find that average spatial concentration was much lower in the late 20th - than in the late 19th - century and that this was the outcome of a continuing reduction over time. Second, the persistent tendency to greater spatial dispersion was characteristic of most manufacturing industries. Third, even so, economically and statistically significant spatial concentration was pervasive throughout this period.
Keywords: N62; N92; R12; 330; manufacturing belt; spatial concentration; transport costs; Industrieregion; Räumliche Verteilung; Industriegeschichte; Schätzung; USA